Effective Power Consumption Monitoring of Smart meter through IoT. Issue 3 (December 2020) - Ravi, V.; Sanjay Kumar, S.; Rajendra Prasad, Ch.; Ramchandar Rao, P.
Abstract: Now a day's electricity consumption in residential homes day by day is increasing. For verification and keep monitoring is very critical task because we have to go physically to take the meter readings in meter existing room. Well it is essential for a consumer because according to the electricity consumed the amount will be charged. We can automate the framework or system by checking the energy meter readings over the web. Our proposed system utilizes microcontroller with energy meter to track the electricity power consumed. With using of GSM module we can transmit the consumed units along with amount charged to the web portal so that consumer can monitor the data over the web. This allows the consumers can check the cost charged and power consumed units online by utilizing a simple web application. Therefore the consumers can monitor the energy meter readings very easily along with the cost and also consumers can check the bill amount online itself. FOTA(Firmware Over-The-Air) option is also available with this option one can update the firmware remotely. FOTA is required if any bugs are available in existing software so to remove the bugs we are updating the firmware remotely. The need of FOTA to remove the bugs in existing software so that we can remotely access particular device and update the version easily.